THE EFFECTIVENESS OF USING PROBLEM POSING IN IMPROVING STUDENTS READING COMPREHENSION - Oktafiona, Sellania; Sada, Clarry; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui efektivitas penggunaan teknik Problem Posing dalam meningkatkan pemahaman membaca siswa kepada mahasiswa semester pertama dari Pendidikan Bahasa Inggris Program Mahasiswa Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura Pontianak, sehingga metode yang tepat adalah dengan menggunakan teknik penelitian eksperimental. Data diperoleh dengan menggunakan teknik pengukuran berupa tes pilihan ganda yang terdiri dari 20 soal dan diterapkan dalam Pre-Test dan Post-Test. Sampel terdiri dari 25 siswa. Hasil dari penelitian ini menunjukkan bahwa teknik Problem Posing efektif untuk mengajarkan pemahaman membaca. T-test (3,18) lebih tinggi dari t-tabel (2,06) pada tingkat signifikansi 5%. Berdasarkan perhitungan ukuran efek, penggunaan teknik Problem Posing efektif untuk meningkatkan kemampuan siswa dalam memahami teks, dengan skor ES> 0,9 yang dikategorikan tinggi. Kata Kunci: Problem Posing, Pre-Experimental, Keefektivitasan Abstract: The purpose of this research is to investigate the effectiveness of using problem posing technique in improving students reading comprehension to the first semester students of the English Education Program Students of Teacher Training and Education Faculty of Tanjungpura University Pontianak, thus the appropriate method applied was pre-experimental research. The data was obtained by using measurement technique in form of multiple choice tests consisted of 20 items which was applied in Pre-Test and Post-Test. The sample consisted of 25 students. The finding of this research showed that Problem Posing Technique was effective to teach reading comprehension. The t-test (3,18) is higher than the t-table (2,06) on the level of significance 5%. Based on the computation of effect size, the use of Problem Posing Technique was effective to increase the student ability in comprehending the text, the score of ES > 0,9 and categorized as high. Keywords: Problem Posing, Pre-Experimental, Effectiveness